MEMAKNAI KATA ‘WAJIB’ DALAM PASAL 31 AYAT (1) UNDANG-UNDANG NOMOR 24 TAHUN 2009 TENTANG BENDERA, BAHASA, LAMBANG NEGARA, DAN LAGU KEBANGSAAN - Eko Rial Nugroho (Lafadz Jaya Publisher, 2023)
The issuance of Law Number 24 of 2009 concerning Flags, Language and State Symbols and the National Anthem, especially Article 31 paragraph (1) brings complications in international business transactions. Although the obligation to use the Indonesian language in a memorandum of understanding or agreement is to be welcomed, lawmakers do not think long and hard about the consequences of this provision for the business world, especially in international business transactions. The use of the phrase